Hi guys! Got a question which I need help...

If a sequence {Xn} is defined in a linear recurrence form, it means that

X(n+1) = aXn + b where a and b are constants. The first four terms of the sequence are 27, -13, 11, -3.4, ...

(i) Find X(n+1) in terms of Xn with X1 = 27

(ii) BY re-arranging your ans in (i) into the form Xn+1 - k = a(Xn - k), where k is a constant to be determined, show that Xn = 25(-0.6)^(n-1) + 2, n = 1,2, ...

I managed to solve part (i) by solving a pair of simultaneous EQNs and got

X(n+1) = -0.6Xn + 3.2 which is the correct ans to (i) but I can't do (ii). Can't see any relationship between my ans in (i) and the EQN given in (ii)...

Thanks in advance!!!